Adolescent diets: balanced nutrition education to achieve optimal nutritional status - Parlin Dwiyana; Annisa Nursita Angesti; Ratna Mutu Manikam; Dahlia Nurdini (Universitas Muhammadiyah Magelang, 2023)
Balanced nutrition practices include knowledge and attitudes towards consuming balance nutritious foods and implementing healthy behaviors. Selection of a balanced nutritional menu and good nutrition intake will determine optimal nutritional and health status. The community service activity in the form of counseling on a balanced nutritional diet for Students of SMKN 24 Cipayung East Jakarta are an effort to achieve optimal nutritional status in adolescents and are expected to be an important momentum to remind the public, especially adolescents, about the importance of balanced nutrition and how to choose healthy and nutritious food. This community service is in the form of providing education regarding a balanced nutritional diet for adolescents. The assessment was carried out using a pre-test before counseling and a post-test after counseling. The educational results revealed an increase in knowledge about a balanced nutritional diet of 14.83 points, from an average value of 63.50 (before counseling) to 78.33 (after counseling). The different test results obtained a p-value of 0.0005. It can be concluded that there is an increase in students' knowledge about a balanced nutritional diet after counseling.